2017
DOI: 10.1155/2017/1320457
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Regression Equation for Predicting Visual Outcomes after Surgical Repair of Open Globe Injuries

Abstract: Background. To analyze the effects of factors other than the ocular trauma score parameters on visual outcomes in open globe injuries. Methods. Open globe injuries primarily repaired in our hospital were reviewed. The number of surgeries, performance of pars plana vitrectomy (PPV), lens status, affected tissues (corneal, scleral, or corneoscleral), intravitreal hemorrhage, intraocular foreign body, glaucoma, anterior segment inflammation, loss of iris tissue, cutting of any prolapsed vitreous in the primary su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Ten patients were treated for suspected endophthalmitis, giving a rate of 2.6%. This is comparable to other studies ranging from 1% to 2% 11,23,37 to 12%. 38 Being a child (50% of cases) and having an IOFB (40% of cases) seemed to carry the greatest risk although total numbers were small.…”
Section: Discussionsupporting
confidence: 91%
“…Ten patients were treated for suspected endophthalmitis, giving a rate of 2.6%. This is comparable to other studies ranging from 1% to 2% 11,23,37 to 12%. 38 Being a child (50% of cases) and having an IOFB (40% of cases) seemed to carry the greatest risk although total numbers were small.…”
Section: Discussionsupporting
confidence: 91%
“…Ocular morbidity included corneal laceration in all cases and uveal involvement in 5 of 9 cases, which is known to portend poor long-term visual recovery. 14 Three of 9 patients had retinal detachments necessitating further surgery.…”
Section: Discussionmentioning
confidence: 97%
“…Seven of 9 cases involved the driver and 8 of 9 involved the eye on the same side as the shattered sideview mirror (1 case did not report vehicle laterality). Ocular morbidity included corneal laceration in all cases and uveal involvement in 5 of 9 cases, which is known to portend poor long-term visual recovery . Three of 9 patients had retinal detachments necessitating further surgery.…”
Section: Discussionmentioning
confidence: 99%
“…4 shows that after three surgeries, patients have no further improvement and reach a plateau vision of about 2 logMAR, which equals hand motion. Gursoy et al found that number of surgeries did not have a significant effect on final BCVA [36]. Therefore, surgical procedures should be considered especially with regard to patient age, condition and risk of general anesthesia.…”
Section: Therapymentioning
confidence: 99%